Factors controlling the spatial distribution of soil organic carbon in the Chinese medicine producing area of NW China1 - He, Mingzhu; Tang, Liang; Li, Chengyi; Ren, Jianxin (Frontiers in Soil Science, 2022)
Soil organic carbon is an important factor for the cultivation and production of traditional Chinese medicine. This study aimed to reveal the spatial distribution of the soil organic carbon density (SOCD) and the effects of the climate, topography, and human activities in Longxi County (Gansu Province, China). The soil organic carbon (SOC) from 200 fixed sampling points were collected and analysed in 2018. Results showed that the total SOCD was 2.67 ± 1.02 kg m-2, while the SOCDs at a soil depth of 0–10, 10–30, and 30–50 cm were 0.63 ± 0.17, 1.10 ± 0.38, and 0.93 ± 0.48 kg m-2, respectively. The temperature, precipitation, elevation, and stream power index showed significant correlations with the SOCD at each soil layer. With an increasing soil depth, the correlation between the slope, relief amplitude, surface roughness, and SOCD gradually decreased. From the central plains to the mountainous areas, the SOCD increased with rising elevation, while the valley plain that formed by the river basin showed low levels of SOCD. In the planting area of traditional Chinese medicine, human activities also had an important impact on the levels of SOCD; namely, the townships with larger per capita arable land had lower SOCD levels and the townships with more investment per unit area maintained higher SOCDs. Therefore, the scientific management of soil fertility and the development of precision agriculture, combined in a soil testing fertilization formula, will guarantee the healthy development of the Chinese herbal medicine planting.